HIV-1 antibodies from infection and vaccination: insights for guiding vaccine design - Bonsignori, Mattia (2012)
Attempts to formulate a protective HIV-1 vaccine through classic vaccine design strategies have not been successful. Elicitation of HIV-1-specific broadly neutralizing antibodies (bnAbs) at high titers that are present before exposure might be required to achieve protection. Recently, the application of new technologies has facilitated the study of clonal lineages of HIV-1 envelope (Env) antibodies, which have provided insights into HIV-1 antibody development during infection and upon vaccination. Strategies are being developed for the analysis of infection and vaccine candidate-induced antibodies, their gene usage, and their maturation pathways such that this information can be used to attempt to guide rational vaccine design.